A 3-Dimensional Printed Aortic Arch Template to Facilitate the Creation of Physician-Modified Stent-Grafts. (October 2018) - Rynio, Pawel; Kazimierczak, Arkadiusz; Jedrzejczak, Tomasz; Gutowski, Piotr
Purpose: To demonstrate the utility of a 3-dimensional (3D) printed template of the aortic arch in the construction of a fenestrated and scalloped physician-modified stent-graft (PMSG).Case Report: A 73-year-old woman with descending thoracic aneurysm was scheduled for thoracic endovascular aortic repair after being disqualified for open surgery. Computed tomography angiography (CTA) revealed no proximal landing zone as the aneurysm began from the level of the left subclavian artery, so a fenestrated/scalloped PMSG was planned. To facilitate accurate placement of the openings in the graft, a 3D printed aortic arch template was prepared from the CTA data and gas sterilized. In the operating room, a Valiant stent-graft was inserted into the 3D printed template and deployed. Using ophthalmic cautery, a fenestration and a scallop were created; radiopaque markers were added. The PMSG was successfully deployed with no discrepancy between the openings and the target vessels.Conclusion: A 3D printed aortic arch template facilitates handmade fenestrations and scallops in PMSGs and may improve accuracy and quality.